Pilot Study Peran Penggunaan Augmented Reality (AR) Dalam Meningkatkan Keputusan Belanja Produk Online - Stone, Alisia Silver; Azwardi, Azwardi; Fitrianto, Mohammad Eko (Forum Kerjasama Pendidikan Tinggi, 2025)
The rapid advancement of digital technology has led to the emergence of Augmented Reality (AR) as an interactive innovation in e-commerce. However, many consumers still experience uncertainty regarding the suitability of products purchased online. This study aims to analyze the role of AR usage in enhancing actual purchase decisions for cosmetic products in online shopping. A descriptive quantitative approach was applied, involving 56 female respondents aged 18–35 who had prior experience shopping for cosmetics using AR features. Data were collected through an online questionnaire and analyzed descriptively. The results show that 53.6% of respondents found AR features very helpful and 30.4% found them quite helpful in ensuring product suitability and increasing purchase confidence. Furthermore, 51.8% of respondents considered AR very easy to use, indicating that this technology provides tangible benefits in the decision-making process. The main challenges identified were poor internet connection, limited device compatibility, and lack of information about AR availability. This study concludes that the use of AR plays a significant role in strengthening consumer confidence and actual purchase decisions, offering valuable implications for developing digital marketing strategies based on interactive consumer experiences.